Oral manifestation in a pediatric patient with pentasomy x. A case report - Acosta de Camargo, María Gabriela (2023)
Aim: To describe the oral finding, physical features and medical features with the genetic diagnosis of a Pentasomy X. Case report: A 6-year-old female patient was referred for oral evaluation presenting acute pain related to ulcers in the attached gingival and dorsum of tongue mucosa. Medical history revealed Pentasomy X associated with interatrial communication, convergent strabismus, recurrent seizures, dysautonomia, episodes of thrombosis and cognitive delay with limited oral communication skills. A palliative oral treatment was applied. Oral hygiene improvement and surveillance were decided considering the absence of dental hypersensitivity, post eruptive enamel breakdowns or dental caries. Less than 30 cases had been reported in the literature, reflecting the rare nature of this genetic disorder and with great difficulties to perform dental treatment. As regards the oral health status of these patients, with an emphasis on dental care, information is totally lacking. Conclusion: Oral care in patients with genetic syndromes must consider the status in general health to prevent medical complications associated with oral disease or dental treatment. Minimal intervention and surveillance are appropriate options in customized therapy.